Efficacy and adverse reaction management of oncolytic viral intervention combined with chemotherapy in patients with liver metastasis of gastrointestinal malignancy - Zhang, Jie; He, Qianyun; Mao, Dongliang; Wang, Chen; Huang, Lei; Wang, Mei; Zhang, Jun (Frontiers in Oncology, 2023)
Background: The liver is a key target organ for colorectal and gastric cancer metastasis. Management of liver metastasis is one of the priorities and difficulties in the treatment of colorectal and gastric cancers. This study aimed to investigate the efficacy, adverse effects, and coping strategies of oncolytic virus injection in patients with liver metastases of gastrointestinal malignancies. Methods: Retrospective analysis of patients treated at Ruijin Hospital affiliated with Shanghai Jiao tong University School of Medicine from June 2021 to October 2022. 47 patients with gastrointestinal liver metastasis were included in the study. The data, including clinical manifestations, imaging, tumor markers, postoperative adverse reactions, psychological intervention, dietary guidance, and adverse reaction management, were evaluated. Results: Oncolytic virus injection was successful in all patients, and no drug injection-related deaths occurred. The adverse effects, such as fever, pain, bone marrow suppression, nausea, and vomiting, were mild and resolved subsequently. Based on the comprehensive intervention of nursing procedures, the postoperative adverse reactions of patients were effectively alleviated and treated. None of the 47 patients had any puncture point infections, and the pain caused by the invasive operation was relieved quickly. After 2 courses of oncolytic virus injection, postoperative liver MRI showed lesion reduction in target organs in 47 patients, including 5 partial remissions, 30 stable diseases, and 12 progressive diseases. Besides, carcinoembryonic antigen showed a decreasing trend. Conclusion: The comprehensive intervention based on nursing procedures after oncolytic virus intervention can ensure the smooth treatment of recombinant human adenovirus type 5 in patients with liver metastases of gastrointestinal malignant tumors, which is of great significance for clinical treatment. It greatly reduces patient complications and improves the patient's quality of life, which can be used in the clinical care of such patients.